DNA methyltransferase mediates the hypermethylation of the microRNA 34a promoter and enhances the resistance of patient-derived pancreatic cancer cells to molecular targeting agents. (October 2020) - Ma, Yan; Chai, Ningli; Jiang, Qiyu; Chang, Zhengyao; Chai, Yantao; Li, Xiaojuan; Sun, Huiwei; Hou, Jun; Linghu, Enqiang
Graphical abstract: Abstract: DNA methyltransferase (DNMT) participates in the transformation or progression of human cancers by mediating the hypermethylation of cancer suppressors. However, the regulatory role of DNMT in pancreatic cancer cells remains poorly understood. In the present study, we demonstrated that DNMT1 repressed the expression of microRNA 34a (miR-34a) and enhanced the activation of the Notch pathway by mediating the hypermethylation of the miR-34a promoter. In patients with pancreatic cancer, the expression levels of DNMT1 were negatively related with those of miR-34a. Mechanistically, knockdown of DNMT1 decreased the methylation of the miR-34a promoter and enhanced the expression of miR-34a to inhibit the activation of the Notch pathway. Downregulation of the Notch pathway via the DNMT1/miR-34a axis significantly enhanced the sensitivity of pancreatic cells to molecular targeting agents. Therefore, the results of our study suggest that downregulation of DNMT enhances the expression of miR-34a and may be a potential therapeutic target for pancreatic cancer.